Promoting the Hidden Paradise of Likupang through Digital Marketing - Lingkan Easter Tulung; Daud M. Liando; Leviane J. H. Lotulung (Jurnal Spektrum Komunikasi, 2024)
Likupang is located on the northern coast of North Sulawesi and has been designated as a super-priority tourist destination. It is surrounded by clear waters, white sandy beaches, green hills, and consists of several small islands. The development of the tourism sector in Likupang increases the region's revenue generated from tourist visits. However, the number of tourists visiting North Sulawesi decreased dramatically during the period of the Covid-19 outbreak, and slightly increased in the transition period, still far below the outbreak. The use of digital marketing communication can be maximized as an effective promotional tool to reach a wider audience. The purpose of this study is to describe the use of digital marketing communication to build destination image in order to attract tourists to visit Likupang. The method used is qualitative research with data collection techniques through observations, documentation study, and interviews with several informants including local government officials, the private sector, as well as tourists. The research results show that the use of digital marketing communication, especially through social media platforms such as Instagram and YouTube, plays a significant role in promoting Likupang. However, the official tourism department websites of the government provide very limited information about the tourism sector. In addition, visual content, particularly photo and video posts, can enhance the attractiveness of the destination and build destination image by featuring the beauty and uniqueness of the coastal scenery, islands, hills, and tourist activities, which become strong attractions for tourists visiting Likupang.